The roommate - Danan, Rosie (Jove, 2020)
"House Rules: Do your own dishes. Knock before entering the bathroom. Never look up your roommate online. The Wheatons are infamous among the east coast elite for their lack of impulse control, except for their daughter Clara. She's the consummate socialite: over-achieving, well-mannered, predictable. But every Wheaton has their weakness. When Clara's childhood crush invites her to move cross-country, the offer is too much to resist. Unfortunately, it's also too good to be true. After a bait-and-switch, Clara finds herself sharing a lease with a charming stranger. Josh might be a bit too perceptive-not to mention handsome-for comfort, but there's a good chance he and Clara could have survived sharing a summer sublet if she hadn't looked him up on the Internet... Once she learns how Josh has made a name for himself, Clara realizes living with him might make her the Wheaton's most scandalous story yet. His professional prowess inspires her to take tackling the stigma against female desire into her own hands. They may not agree on much, but Josh and Clara both believe women deserve better sex. What they decide to do about it will change both of their lives, and if they're lucky, they'll help everyone else get lucky too"--